Stomatopod and decapod crustaceans from Camamu Bay, state of Bahia, Brazil - de Almeida, Alexandre Oliveira; Guerrazzi, Maria Cecqlia; Coelho, Petr]Nio Alves (Zootaxa, 2007)
Camamu Bay, located on the central coast of the state of Bahia, Brazil (13°47’ to 14°10’S), is the third-largest Brazilian bay. It is included in a zone that perhaps constitutes the last unexplored frontier on the Brazilian coast, situated between Todos os Santos Bay in Bahia, and the city of Vitória in Espírito Santo. Moreover, this zone coincides with an area of remarkable zoogeographical interest, the transition zone between the Brazilian and Paulista provinces. Camamu Bay contains a wide diversity of marine environments such as sandy beaches, rocky substrata, and mangroves, and it is still in a good state of preservation compared to other large Brazilian bays. The objective of this study was to survey the fauna of Crustacea (orders Stomatopoda and Decapoda) in Camamu Bay. The material analyzed was collected by trawling from July 2003 to September 2005. Voucher specimens were deposited in the collections of the Universidade Estadual de Santa Cruz and the Universidade Estadual do Sudoeste da Bahia, located in the cities of Ilhéus and Jequié (state of Bahia, Brazil), respectively. A total of 93 species, belonging to 35 families, was collected. The order Stomatopoda was represented by 3 families and 4 species; the order Decapoda was represented by 31 families and 89 species. The most important family in terms of number of species was Alpheidae, with 11 species. Of the total number of species, 88 are recorded from Camamu Bay for the first time, while 10 species are cited from the state of Bahia for the first time. The southern geographical distributional limits in the western Atlantic for the caridean Synalpheus pandionis and the brachyurans Macrocoeloma laevigatum and Elamena gordonae are extended.